Learners' anxiety and willingness to communicate among polytechnic students in learning English language - Maizan binti Mohamad
Learning a second language such as English is a challenging task for many language learners due to various psychological factors such as anxiety and unwillingness to communicate in the language. Although the two factors individually are said to contribute to the success or failure in learning the language, it is not clear whether the interplay between anxiety and willingness to communicate is present or not. In relation to this, the current study primarily aims to investigate the levels of foreign language anxiety (FLA), find out levels of willingness to communicate in English (WTC), and find out the correlation between language anxiety and the willingness to communicate in English among students. Quantitative approach was employed whereby data were collected using two instruments; the Foreign Language Classroom Anxiety Scale (FLCAS) and the Willingness to Communicate Scale (WTCS). The questionnaires were administered to 123 diploma students at Politeknik Hulu Terengganu. Using SPSS 22.0, data were analysed descriptively, namely minimum, maximum, mean, and standard deviation, and data were also analysed inferentially, namely independent sample t-test and correlation. The findings revealed that most students experienced a moderate level of English language anxiety. In addition, there was a significant difference in the learners' language anxiety in English language classrooms based on gender, whereby female students were more anxious than males. The female students were found to be statistically significantly more anxious than the male students. Besides that, students also reported having a very low willingness to communicate in the English language. The study also revealed that there were significant negative correlations between students' FLCAS and their WTC. Anxiety is common among learners of English as Second Language (ESL). The study provides several pedagogical implications to both ESL students and practitioners. They could potentially guide educators in improving their teaching and learning process by creating a more conducive and stress-free environment to encourage students to communicate more confidently. This new environment will hopefully enhance students' performance, especially in using the English language to communicate.